Learning to talk : stories - Mantel, Hilary, 1952- (Henry Holt and Company, 2022)
"In the wake of Hilary Mantel's brilliant conclusion to her award-winning Wolf Hall trilogy, this collection of loosely autobiographical stories locates the transforming moments of a haunted childhood. Sharp and funny, these drawn-from-life stories begin in the 1950s in an insular northern village "scoured by bitter winds and rough gossip tongues." For the child narrator, the only way to survive is to get up, get on, get out. In "King Billy Is a Gentleman," the child must come to terms with the loss of a father and the puzzle of a fading Irish heritage. "Curved Is the Line of Beauty" is a story of friendship, faith, and a near-disaster in a scrap-yard. The title story sees our narrator ironing out her northern vowels with the help of an ex-actress with one lung and a Manchester accent. In "Third Floor Rising," she watches, amazed, as her mother carves out a stylish new identity. With a deceptively light touch, Mantel illuminates the poignant experiences of childhood that leave each of us forever changed"--